Using voluntary reports from physicians to learn from diagnostic errors in emergency medicine. Issue 4 (3rd November 2015) - Okafor, Nnaemeka; Payne, Velma L; Chathampally, Yashwant; Miller, Sara; Doshi, Pratik; Singh, Hardeep
Abstract : Objectives: Diagnostic errors are common in the emergency department (ED), but few studies have comprehensively evaluated their types and origins. We analysed incidents reported by ED physicians to determine disease conditions, contributory factors and patient harm associated with ED-related diagnostic errors. Methods: Between 1 March 2009 and 31 December 2013, ED physicians reported 509 incidents using a department-specific voluntary incident-reporting system that we implemented at two large academic hospital-affiliated EDs. For this study, we analysed 209 incidents related to diagnosis. A quality assurance team led by an ED physician champion reviewed each incident and interviewed physicians when necessary to confirm the presence/absence of diagnostic error and to determine the contributory factors. We generated descriptive statistics quantifying disease conditions involved, contributory factors and patient harm from errors. Results: Among the 209 incidents, we identified 214 diagnostic errors associated with 65 unique diseases/conditions, including sepsis (9.6%), acute coronary syndrome (9.1%), fractures (8.6%) and vascular injuries (8.6%). Contributory factors included cognitive (n=317), system related (n=192) and non-remedial (n=106). Cognitive factors included faulty information verification (41.3%) and faulty information processing (30.6%) whereas system factors included high workload (34.4%) and inefficient ED processes (40.1%). Non-remediable factors included atypical presentation (31.3%) and the patients' inability to provide a history (31.3%). Most errors (75%) involved multiple factors. Major harm was associated with 34/209 (16.3%) of reported incidents. Conclusions: Most diagnostic errors in ED appeared to relate to common disease conditions. While sustaining diagnostic error reporting programmes might be challenging, our analysis reveals the potential value of such systems in identifying targets for improving patient safety in the ED.